THE ROLE OF COMMUNICATION IN INFLUENCING THE ENTREPRENEURIAL INTENTION OF SMALLHOLDER SHEEP FARMING IN WEST JAVA - Adji, Riyanto; Dimyati, Dindin (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The traditional sheep farming process is carried out by smallholder sheep farmers in West Java based on the inheritance passed down from their parents. A more detailed examination of the process of cultivating people's sheep reveals significant economic potential, encompassing the upstream sub-sector, the on-farm sub-sector, and the downstream sub-sector. This lucrative business opportunity is challenging for smallholder sheep farming to attain, partly due to difficulties in communication. The objective of this study is to gain insight into the communication factors that influence the entrepreneurial spirit of smallholder sheep farming in West Java. This study employs three variables: communication frequency, communication quality, and information sources. This research employs a quantitative analytical method of the causal-comparative research type. The analysis yielded findings indicating that communication techniques play a pivotal role in influencing the entrepreneurial spirit of smallholder sheep farming